Tuduhan Afiliasi PKI dalam Ronggeng Dukuh Paruk : (Sebuah Kajian Sosiologi) - A Rizki Wahyu Pradana; Luki Alifvia; Mochammad Ryan Syazaki; Mohamad Afrizal (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
This article examines the accusations of PKI affiliation contained in the novel Ronggeng Dukuh Paruk Ahmad Tohari's work, with a literary sociology approach. This novel describes the lives of village communities are hit by social and political tensions after the incident G30S/PKI. Through the main character Srintil, a ronggeng who is trapped in stigma politics, this article analyzes how accusations of PKI affiliation affect social dynamics and culture in the village. The focus of this study is to understand how social elements, especially gender and the role of women in Batak custom, interact with greater political power, and how this is reflected in the novel's narrative structure. By using literary sociology theory, this research also discusses identity social and political aspects are formed through literary texts, as well as the implications of these accusations on the formation of morality and views of society at that time. Through analysis It is hoped that this article will contribute to the understanding of the relationship between literature, politics and social identity in Indonesia, especially in context post-1965 history.